Interventions for obstructive uropathy in advanced prostate cancer: a population‐based study. (12th May 2022) - Nathan, Arjun; Morris, Melanie; Parry, Matthew G.; Berry, Brendan; Sujenthiran, Arunan; Nossiter, Julie; Payne, Heather; Van Der Meulen, Jan; Clarke, Noel W.; Green, James S. A.
Abstract : Objectives: To develop and validate a coding framework to identify interventions for upper tract obstructive uropathy (UTOU) in men with locally advanced and metastatic prostate cancer (PCa) using administrative hospital data to assess clinical outcomes. There are no population‐based studies on the incidence, treatment, and outcomes of this complication. Patients and Methods: Patients newly diagnosed with PCa between April 2014 and March 2019 were identified in the English cancer registry. A coding framework based on procedure (Office of Population Censuses and Surveys Classification of Surgical Operations and Procedures fourth edition) and diagnostic (International Classification of Diseases, 10th edition) codes was developed and validated. Subsequent clinical outcomes were determined using Hospital Episodes Statistics to determine the utility of the intervention. Results: A total of 77 010 patients newly diagnosed with locally advanced, and 30 083 patients with metastatic PCa were identified. Of these, 1951 (1.8%) patients underwent an intervention for UTOU according to our coding framework: 830 (42.5%) had locally advanced disease and 1121 (57.5%) had metastatic disease. In all, 844 (43.3%) had a percutaneous nephrostomy (PCN), 473 (24.2%) had a PCN with antegrade stent, and 634 (32.5%) had a retrograde stent. The mean follow‐up was 43.2 months. The cumulative incidence of the use of these interventions at 1, 3, and 5 years was 2.5%, 3.6% and 4.2% in men with metastases compared to 0.5%, 0.9% and 1.4% in men with locally advanced disease. Conclusion: A new coding framework, developed to identify procedures for UTOU was applied in the largest study to date of UTOU in men with primary locally advanced and metastatic PCa. Results demonstrated that 2% of men with locally advanced PCa and 4% of men with metastatic PCa require an intervention to resolve UTOU within 5 years of their PCa diagnosis.